Single Processing versus Parallel-Based Processing on Web Server: Which Has the Best Performing Service - Ria Andryani; Edi Surya Negara; Ferdiansyah (Institute of Information Technology and Social Science (IITSS), 2020)
A quality server service is a server that is capable of delivering quality services to all of the servers that access the server services. Quality service is a service that guarantees conficonfidentiality, integrity, and availability. Parallel based service on a server or load balancing is one of the means used to improve the performance and availability of servers, is to divide the requests are coming to multiple servers at once, so that the load borne by each lighter. So due to get a lighter workload then directly affect the performance of servers are increasingly responsive, the level of availability server can also be maintained. By using load balancing technology, then there will be a difference in the performance of Web Server Load Balancing with Single Server, which can be used as a comparison, so it can be a solution for managing Server.